2015
DOI: 10.1007/s00134-015-3952-5
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care ultrasound in intensive care units: assessment of 1073 procedures in a multicentric, prospective, observational study

Abstract: With regard to guidelines, POCUS utilization for procedural guidance remains insufficient. In contrast, POCUS for diagnostic assessment is of extensive use. Its impact on both diagnosis and treatment of ICU patients seems critical. This study identified factors associated with an improved clinical value of POCUS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
97
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(105 citation statements)
references
References 38 publications
4
97
0
4
Order By: Relevance
“…Some numbers allow us to affirm this concept. A recent multicenter study involving 142 adult intensive care unit (ICU) patients of France, Belgium and Switzerland [2], showed that point-of-care US (POCUS) was used in approximately one-third (36 %) of the patient population/day, predominantly for diagnostic purposes in 87 % of the cases, whereas for interventional guidance was used in only 13 % of indications.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Some numbers allow us to affirm this concept. A recent multicenter study involving 142 adult intensive care unit (ICU) patients of France, Belgium and Switzerland [2], showed that point-of-care US (POCUS) was used in approximately one-third (36 %) of the patient population/day, predominantly for diagnostic purposes in 87 % of the cases, whereas for interventional guidance was used in only 13 % of indications.…”
Section: Dear Editormentioning
confidence: 99%
“…Some numbers allow us to affirm this concept. A recent multicenter study involving 142 adult intensive care unit (ICU) patients of France, Belgium and Switzerland [2], showed that point-of-care US (POCUS) was used in approximately one-third (36 %) of the patient population/day, predominantly for diagnostic purposes in 87 % of the cases, whereas for interventional guidance was used in only 13 % of indications.Reasoning about these findings, it is intuitive asking how were managed the remaining 64 % (the most) who did not receive an US-based approach.It is supposed that deliberate US use is not a routine practice in intensive care settings, but according to diagnostic and procedural guidance capabilities of this noninvasive and indolent diagnostic imaging method, why not to extend POCUS to a 100 % of the patient population/day is a logical question that could naturally arise.Limitations for using POCUS are probably multiple, ranging from the common physicianś believe that US is a merely ''operator-dependent'' method, passing through the unproven fact that US has never demonstrated survival benefits to critically ill patients, up to the scarce monetary resources to purchase and maintain an ultrasound machine, being the last specially relevant in developing countries.It seems that a lot of reasons for not using POCUS exist; however, there is still an important amount of uncertainty from practitioners about using US, mostly related to the skepticism related to a technique which, at first glance, does not belong to the scope of intensivists.We encourage intensivists to change their work path from the traditional paradigm to the US-supported paradigm if they have not already done so. Benefits are clearly demonstrated for patients and also physicians and nurses working in ICU.…”
mentioning
confidence: 99%
“…In routine, echocardiography is often used to estimate LVEF (15). However, LVEF is a load-dependent index, which does not reflect only cardiac contractility.…”
Section: Commentarymentioning
confidence: 99%
“…Dans une enquête publiée en 2015 et concernant plusieurs pays européens, plus d'un tiers des patients de réanimation bénéficiaient d'au moins un examen échographique par jour, que ce soit à visée diagnostique ou pour guider une procédure invasive [1]. Chez ces patients, l'échocardiographie était l'examen le plus fréquemment réa-lisé et avait un impact thérapeutique important.…”
unclassified